(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the suitability of the training program to improve the knowledge of health staff on early detection - early intervention for children with disabilities in Quang Nam in 2022. Research method: Cross-sectional study. Information was collected from a quantitative sample of 81 people, in-depth interviews with 10 health staff at all levels and lecturers of the training program. Results: Over 90% of the research subjects generally evaluated the training course to improve the knowledge of health staff on early detection - early intervention for children with disabilities in Quang Nam as good and very good. The training location was good or better, accounting for over 86%; the training time was reasonable, reaching a good level of over 71%. However, this training course still has some limitations: little practice time, a lot of theoretical knowledge, so it takes time to absorb and apply, the theoretical content should be supplemented with illustrative images and videos. Conclusion and recommendations: It is necessary to maintain training programs for health staff on early detection and early intervention of disabilities. Training content must be appropriate to the training duration. If the training duration is short, it is necessary to divide the training content into smaller parts to ensure that health staff can practise on that content. Increase the time for practical instruction and apply theoretical knowledge to practise. Training class lectures also need to be improved to be more vivid and richer …